Elastic Moduli of Breast and Prostate Tissues under Compression - Krouskop, Thomas A.; Wheeler, Thomas M.; Kallel, Faouzi; Garra, Brian S.; Hall, Timothy (Ultrasonic imaging, 1998)
To evaluate the dynamic range of tissue imaged by elastography, the mechanical behavior of breast and prostate tissue samples subject to compression loading has been investigated. A model for the loading was validated and used to guide the experimental design for data collection. The model allowed the use of small samples that could be considered homogeneous; this assumption was confirmed by histological analysis. The samples were tested at three strain rates to evaluate the viscoelastic nature of the material and determine the validity of modeling the tissue as an elastic material for the strain rates of interest. For loading frequencies above 1 Hz, the storage modulus accounted for over 93 percent of the complex modulus. The data show that breast fat tissue has a constant modulus over the strain range tested while the other tissues have a modulus that is dependent on the strain level. The fibrous tissue samples from the breast were found to be 1 to 2 orders of magnitude stiffer than fat tissue. Normal glandular breast tissue was found to have an elastic modulus similar to that of fat at low strain levels, but the modulus of the glandular tissue increased by an order of magnitude above fat at high strain levels. Carcinomas from the breast were stiffer than the other tissues at the higher strain level; intraductal in situ carcinomas were like fat at the low strain level and much stiffer than glandular tissue at the high strain level. Infiltrating ductal carcinomas were much stiffer than any of the other breast tissues. Normal prostate tissue has a modulus that is lower than the modulus of the prostate cancers tested. Tissue from prostate with benign prostatic hyperplasia (BPH) had modulus values significantly lower than normal tissue. There was a constant but not significant difference in the modulus of tissues taken from the anterior and posterior portions of the gland.